Norm-Based Trade Union Membership: Evidence for Germany - Laszlo Goerke; Markus Pannenberg (Institute for the Study of Labor (IZA), 2003)
In the absence of closed-shops and discriminatory wage policies, union membership can be explained by the existence of social norms. We describe a model, incorporating institutional features of the German labour market, which explicitly allows for social custom effects in the determination of union membership. Using panel data for Germany, we find evidence for according effects which restrict freeriding. The impact of social norms tends to increase with net union density. Hence, observed reductions in the demand for union membership can weaken the impact of a norm and accentuate the free-rider problem.
Keywords: J51; D71; 330; Germany; norms; social custom; trade union membership; Gewerkschaftlicher Organisationsgrad; Mitgliedschaft; Soziale Norm; Trittbrettfahrerverhalten; Deutschland